1596 A Retrospective Audit Investigating and Identifying Factors Relating to Delays to Theatre Within Neurosurgery at Leeds - A Tertiary Referral Centre. (12th October 2021) - Chowdhury, M R; Anderson, I; Sheikh, S; Joumah, A; Iqbal, H; Goel, A
Abstract: Aim: Leeds Neurosurgery receives referrals as a tertiary centre from a cohort covering 3 million people, receiving over 9000 referrals in the last year via its online system, Patientpass. This audit aims to identify factors which leads to delays in surgery, especially in light of the COVID-19 pandemic. Method: We looked at 760 patients who were included in the study and used the electronic clinical notes system, PPM+ and also the electronic referral system Patientpass and looked at weekday and date of admission, cranial/spinal admission, diagnosis, age, referring hospital, time taken in theatre, theatre used, intraoperative timings, length of stay and date of discharge. Results: The majority of the cases were either vascular or trauma related. 77.2% of surgeries were either same day or within 24 hours. The average length of stay was 17 days. The average time in theatre, 2h11m. The designated acute theatres were used approximately 75% of the time. Conclusions: Interestingly, the mean time from admission to theatre was 1.25 days. 225 cases were investigated as a sample randomly selected. It is identified that 30 cases were delayed. 20% were delayed due to imaging requested for surgical management. 6% were due to patients awaiting consultant review. 10% due to awaiting other investigation results (i.e., COVID swab.) There were other identifiable factors such as awaiting 'hot' theatres, reversing coagulopathies and medically deteriorating patients. We have provisionally identified factors and will re-audit this in the next cycle in order to maximise efficiency.